Pengaruh Konsumsi Pangan dan Pengeluaran Pangan Serta Pengetahuan Gizi Ibu Terhadap Balita Stunting Di Wilayah Pinggiran Sungai Kalimantan Selatan - Suhaimi, Ahmad; Rahman , Syarkani; Royensyah , Rum Van; Purna Kusumaya; Eko Agus Mulyo Jati; Misransyah (Rawa Sains: Jurnal Sains STIPER Amuntai, 2022)
Nutritional problems that occur at a certain time will cause development problems in the future. Delay in providing nutrition services will result in severe damage and may even be irreversible. Therefore, efforts to improve nutrition should especially be shown to infants or children under five and pregnant women. Babies today are leaders, scientists, scholars, and workers in the future. They are the next generation of the homeland and nation. This study aims to determine food consumption, food expenditure and nutritional knowledge of housewives and to determine the effect of food consumption, food expenditure and knowledge of maternal nutrition on the incidence of stunting in children under five. This research was conducted in households in the riverbank area of ​​South Kalimantan. This type of associative research, using interviews and multiple linear regression analysis. The results showed that from 180 household samples, 102 respondents (55.66%) with diverse food consumption categories and 78 respondents (43.33%) with non-diverse food consumption categories. Furthermore, for food expenditure there were 120 respondents (66.67%) included in the category of low food expenditure proportion and 60 respondents (33.33%) included in the high food expenditure proportion category. Mother's knowledge about nutrition showed 92 respondents (51.11%) with sufficient knowledge category, and 88 respondents (48.88%) good knowledge. And only the food consumption variable has a dominant effect on the incidence of stunting in children under five who live in households in riverside areas.